Common ownership: Europe vs. the US - Nuria Boot; Jo Seldeslachts; Albert Banal-Esta\~nol (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
Common ownership - when an investor holds shares in two or more companies - has recently attracted significant attention from policy-makers and researchers, studying mainly US firms. European firms, however, are different as top investors with large stakes, like governments, founding families and foundations are much more prevalent. This paper takes a well-known common ownership with micro-economic foundations, lambda, capturing managerial incentives, and compares its implications for S&P Europe 350 firms to those of the S&P 500 for the period 2004-2015 by looking at within, across and global lambda patterns of the European and US S&P companies. We find that US companies have a higher lambda, but European firms' lambda become both faster connected within Europe and across with their US counterpart where the latter is even more pronounced. Both patterns can be traced back to US investment managers' increasing global reach.
Keywords: G23; G32; K15; 330; Ownership structure; S&P 500; S&P 350